1996
DOI: 10.2166/wst.1996.0555
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of DNA in the exopolymeric matrix of activated sludge and bacterial cultures

Abstract: More deoxyribonucleic acid (DNA) was measured than could be accounted for by cell counts in activated sludge flocs, a mixed culture of sludge bacteria, and a pure culture of Pseudomonas putida. This means that estimations of cell number or biomass by measurement and correlation with DNA content will result in an overestimation of the cell number or biomass by up to a factor 10. There could be four reasons for the fact that the DNA was present: There were no specific enzymes present that degrade DNA (DNAses), D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Accordingly, we have shown that the creation of a reducing environment by the addition of DTT readily inactivates S. oneidensis EndA. Also present in S. oneidensis EndA are the aspartic acid and glutamic acid residues that are involved in binding a catalytic divalent metal ion (36 sludge in wastewater treatment plants (46). Substantial amounts of eDNA have also been observed in marine sediments, in which it may represent the major source of phosphorus (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we have shown that the creation of a reducing environment by the addition of DTT readily inactivates S. oneidensis EndA. Also present in S. oneidensis EndA are the aspartic acid and glutamic acid residues that are involved in binding a catalytic divalent metal ion (36 sludge in wastewater treatment plants (46). Substantial amounts of eDNA have also been observed in marine sediments, in which it may represent the major source of phosphorus (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…However, e-DNA occurs in sufficiently high quantities to raise some doubt. In fact, Palmgren and Nielsen reported in 1996 the accumulation of DNA in the EPS matrix of activated sludge and pure cultures of Pseudomonas putida (17). Allesen-Holm et al (1) found that in P. aeruginosa biofilms, the e-DNA is likely derived from whole genomic DNA.…”
mentioning
confidence: 99%
“…Concentrations vary among different environments, ranging from 2 g g Ϫ1 in dry soil (49) to up to 20 mg g Ϫ1 organic matter in activated sludge from wastewater treatment plants (51). The pool of eDNA provides a reservoir for horizontal gene transfer (45,68) and a valuable source of carbon, nitrogen, and, in particular, phosphorus (11,12,48,53).…”
mentioning
confidence: 99%
“…This matrix, which in many cases comprises the majority of the communities' biomass, consists of different biopolymers. It has previously been reported that eDNA is abundant in bacterial biofilms (19,51); in addition, polysaccharides and proteins are common components (18). Studies of Pseudomonas aeruginosa demonstrated that eDNA in the matrix is required for structural integrity during the early stages of biofilm formation (70).…”
mentioning
confidence: 99%